The Relationship between Attitudes, Community Behavior, and Water Dispensers with the Incidence of Dengue Hemorrhagic Fever (DHF) in the Working Area of the Bebesen Primary Health Care, Bebesen District, Central Aceh Regency in 2024 - Zulfikar, Zulfikar; Yudhastuti, Ririh; Haksama, Setya; Iriyanti, Maulina; Saipullah, Saipullah; Putra, Andi Pratama; Siregar, Dharma Yunita; Yusran, Mawadhah (Journal of Ecohumanism, 2025)
Dengue Hemorrhagic Fever (DHF) is a serious infectious disease with high mortality, especially when treatment is delayed and the patient is in shock. This study aimed to assess the relationship between community attitudes, behaviors, and the presence of water dispensers with the incidence of DHF in Bebesen District, Central Aceh Regency, in 2024. Using a cross-sectional design, 55 respondents were selected randomly. Data was collected from August 4 to August 19, 2024. The study employed descriptive analytics and Chi-square tests for statistical analysis. The results showed a significant relationship between community attitudes and the incidence of DHF, with a P value of 0.003, indicating statistical significance. Similarly, the presence of water dispensers was found to significantly affect DHF incidence, with a P value of 0.002. These findings highlight the importance of positive community attitudes and behaviors, as well as the management of water sources, in preventing DHF. It is anticipated that this research will lead to a change in the community’s behavior and enhance DHF prevention measures. Additionally, interdisciplinary collaboration within the Bebesen Primary Health Care is essential for addressing the issue effectively.